2011
DOI: 10.1002/nav.20456
|View full text |Cite
|
Sign up to set email alerts
|

Improving series and parallel systems through mixtures of duplicated dependent components

Abstract: We discuss suitable conditions such that the lifetime of a series or of a parallel system formed by two components having nonindependent lifetimes may be stochastically improved by replacing the lifetimes of each of the components by an independent mixture of the individual components’ lifetimes. We also characterize the classes of bivariate distributions where this phenomenon arises through a new weak dependence notion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It should be pointed out that the results given in the present paper have a narrow intersection with the contribution of Di Crescenzo and Pellerey [7]. First of all, papers [6] and [7] deal with 2-unit series and parallel systems, whereas the systems we examine here have arbitrary fixed sizes. Moreover, the single common case involves random variables K 1 = 1 a.s. and K 2 having binomial distribution with parameters n = 2 and p = 1/2.…”
Section: A Parrondo's Type Paradoxmentioning
confidence: 55%
See 2 more Smart Citations
“…It should be pointed out that the results given in the present paper have a narrow intersection with the contribution of Di Crescenzo and Pellerey [7]. First of all, papers [6] and [7] deal with 2-unit series and parallel systems, whereas the systems we examine here have arbitrary fixed sizes. Moreover, the single common case involves random variables K 1 = 1 a.s. and K 2 having binomial distribution with parameters n = 2 and p = 1/2.…”
Section: A Parrondo's Type Paradoxmentioning
confidence: 55%
“…. , n − 1 (by (7) and Theorem 3.A.34 in Shaked and Shanthikumar [17]), so that K j ≤ icx K j+1 . Hence, if X ≥ st Y then from Theorem 1 we obtain S K j ≤ st S K j+1 for j = 0, 1, .…”
Section: A Parrondo's Type Paradoxmentioning
confidence: 91%
See 1 more Smart Citation
“…Results involving the fact that increasing the randomness in the structure of reliability systems causes a stochastical improvement of the system have been given recently in [11], where it was shown that the lifetime of a series or of a parallel system may be stochastically improved by means of suitable mixtures. See also [12], where the reliability of a system improves by introducing randomness in the number of system components extracted from different batches.…”
Section: Application To the Reliability Of Series Systemsmentioning
confidence: 99%
“…They provided sufficient conditions on the components lifetimes and on the random number of components chosen from the two stocks in order to improve the reliability of the whole system. See, also, Navarro and Spizzichino [16] and Di Crescenzo and Pellerey [5] for the analysis and the comparison of parallel and series systems with heterogeneous components sharing the same copula, or with components linked via suitable mixtures.…”
Section: Introductionmentioning
confidence: 99%